Uji Performa Sudu Turbin Berbahan Polimer Serat Karbon - Wisnu Kusuma Whardana; Erwin Erwin; Slamet Wiyono (Jurnal Asiimetrik: Jurnal Ilmiah Rekayasa Dan Inovasi, 2022)
Sultan Wind Turbine is a vertical type wind turbine researched by New Renewable Energy Lab which is used as development for wind energy utilization. In this wind turbine, there are problems in the form of blade resistance which is not strong enough to withstand wind velocity when the wind blows reaches 4 m/s. The blade, which is one of the parts that have the highest liability on the turbine, can be improved in terms of performance and their overall strength. The blade material which currently used is fibreglass, and Styrofoam can be substituted using a better material to improve its performance. Carbon fiber and ABS filament can be substituted as a blanket and airfoil to be used as materials for manufacturing new blades. This research will focus on improvised blades in terms of performance and strength. With an experimental and quantitative approach, the data obtained from the blades that have been improvised with carbon fiber and ABS filament, resulting in blades that are superior from their predecessors.